1995
DOI: 10.1016/0014-5793(95)00525-e
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of interleukin‐8 receptor in human polymorphonuclear neutrophils by formyl peptide and lipopolysaccharide

Abstract: Interleukin-8 (IL-8) is implicated in the pathogenesisdomain for . We have demonstrated that thiol residues of a large number of neutrophil-driven inflammatory diseases, of the IL-8R participate in the ligand binding and their chemiAlthough the cytokine activates neutrophils through a receptor, cal modification impairs IL-8 mediated functions in neutrophils no information is available regarding the regulation of IL-8 receptor (IL-8R) expression. The present study shows that, compared [12,13]. which triggers ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Neutrophils express the IL-8/GCP-2 receptor CXCR1 and the more promiscuous IL-8/GCP-2/Gro␣/NAP-2/ ENA-78 receptor CXCR2 (47). Previous studies of neutrophils using cLPS as the stimulus have found contrasting evidence of either cLPS-mediated up-regulation of IL-8 binding (27) or cLPSdriven protease-dependent shedding of these receptors (28,29). We observed little regulation of CXCR1 expression by TLR ligands, although this may have become evident over a longer time course, or in the presence of small numbers of monocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophils express the IL-8/GCP-2 receptor CXCR1 and the more promiscuous IL-8/GCP-2/Gro␣/NAP-2/ ENA-78 receptor CXCR2 (47). Previous studies of neutrophils using cLPS as the stimulus have found contrasting evidence of either cLPS-mediated up-regulation of IL-8 binding (27) or cLPSdriven protease-dependent shedding of these receptors (28,29). We observed little regulation of CXCR1 expression by TLR ligands, although this may have become evident over a longer time course, or in the presence of small numbers of monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Contradictory reports have shown that neutrophils respond to cLPS preparations with either an increase in 125 I-labeled IL-8 binding (27) or a protease-dependent shedding of the two major neutrophil chemokine receptors CXCR1 and CXCR2 (28,29). Using flow cytometry, we investigated the roles of TLR2 and TLR4 in mediating down-regulation of these receptors.…”
Section: Tlr-mediated Modulation Of Neutrophil Chemokine Receptor Expmentioning
confidence: 99%
“…There have been several attempts to determine the molecular characteristics of IL-8R by cross-linking studies using radiolabeled ligands. These resulted in the detection of either a single surfaceexpressed molecule (27,28) or multiple variants diverging in molecular size (29,30). The only report providing some evidence for glycosylation of IL-8R (27) did not, however, discriminate between the different receptor types CXCR-1 and CXCR-2, which were only later shown to be coexpressed on neutrophils (31).…”
Section: Discussionmentioning
confidence: 99%
“…Polyclonal human anti-IL-8R antibody was raised in rabbits against 58 kDa receptor protein of human neutrophils, and the anti-IL-8R antibody was characterized by 60-70% binding inhibition of [125I]IL-8 to neutrophils and also by Western blotting analysis [15].…”
Section: Methodsmentioning
confidence: 99%